Congenital ulnar clubhand: epidemiology, classification, clinical picture, treatment - Garbuzniak, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
Congenital ulnar clubhand manifests with different variants of underdevelopment of the forearm and hand, dysfunctions of the elbow and carpal joints, and is classified into IV types. Treatment of children with congenital ulnar clubhand is possible only in a surgical way, the Ilizarov compression-distraction technique being the most widespread approach. Treatment of patients with humeroradial synostosis is the most unfavourable one from the viewpoint of its functional result.